2D INVERSION MODELING OF OIL AND GAS BASINS USING GRAVITY DATA IN TAMBELANG DISTRICT - Gunawan, Belista; Permana, Nanda Ridki (Engineering Faculty Universitas Lampung, 2024)
Pertamina Hulu Energi discovered a new source of oil and gas reserves in Tambelang, Bekasi Regency, which was named East Pondok Aren (EPN-001). These oil and gas reserves have great potential based on the oil flow test in the second Drill Stem Test. The drill data needs to be correlated with other supporting data such as geophysical methods to ensure the accuracy. Therefore, this research was conducted to examine the subsurface structure of oil and gas reserves in EPN-001 through 2D inversion modeling using the gravity method. Gravity satellite data was taken via the GGMPlus website with a total of 23,898 data in the form of gravity disturbance, geoid, and topography, so only terrain and bouguer corrections were carried out to get the Complete Bouguer Anomaly value. The research results show low anomaly values from -0.4463 – (-0.0339) mGal which are thought to be associated with alluvium lithology and the Lower Cibulakan Formation. In the 2D model, it can be seen that the drilling point in the Lower Cibulakan Formation layer has a density contrast value of -0.002 – 0.001 g/cc at a depth of 2590 m, and is known to be a reservoir that stores hydrocarbon reserves in the research area.